ANALISIS RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sari, Fira Mita; Banjarnahor, Haposan (SCIENTIA JOURNAL, 2021)
Every company that is founded has the aim of obtaining a profit, increasing every sale in each period and to improve the welfare of employees and shareholders. The purpose of this study was to determine the effect on profitability, liquidity and activity in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange, by conducting research in the 2015-2019 period. The population in this study is 26 companies that have been listed on the Indonesia Stock Exchange, using the sampling technique, namely purposive sampling and obtaining as many as 10 companies that have met the criteria determined by the researcher. in this study using SPSS version 25.00. The results of the research on the F test indicate that there is a significant influence between profitability, liquidity and activity simultaneously on financial performance by obtaining a sig value of 0.000 <0.05 and in F table 2.807> 255.546 so that the regression model in this study is worthy of research. . whereas in the T test it is concluded that profitability,activity and liquidity have a significant effect on financial performance while activity has no effect on financial performance.